WAYS TO IMPROVE THE EFFICIENCY OF TEXTILE ENTERPRISES' MARKETING PROGRAMS BASED ON DIGITALIZATION (Marketing Journal, 2025)
The article examines the importance and ways of increasing the efficiency of marketing programs in the context of economic digitalization, with a focus on textile and garment enterprises. It is emphasized that marketing programs are a key tool for achievin g tactical business goals. The study shows that the application of automation, artificial intelligence, and digital technologies in modern textile production not only improves product quality but also reduces uncertainty and risks in marketing activities. The authors propose a multi -scenario approach to the development of marketing programs and highlight the potential for its digital implementation. 41
Keywords: competitiveness; digital economy; marketing program; textile industry; automation; artificial intelligence; scenario method